2020
DOI: 10.18488/journal.29.2020.72.236.246
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Profitability of General Insurance Companies in Indonesia

Abstract: This research work shows the impact on profitability by Return on Assets (ROA) on capital adequacy measured by Risk Based Capital (RBC), Return on Investment (ROI) and Solvency by Debt Equity Rate (DER) measured). Then prove the RBC and ROI effect on DER, then demonstrate the RBC 's influence on ROA through DER, demonstrate the ROA impact on the general insurers reported upon on Indonesian Stok Exchange 2015-2018. The design of the research was causal research. Technical sampling using a deliberate method of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…Dimensi finansial meliputi pengembalian aset (ROA), laba atas investasi (ROI), laba atas ekuitas (ROE), pangsa pasar, pertumbuhan penjualan dan profitabilitas. Sedangkan dimensi non-finansial meliputi kepuasan klien, kepuasan karyawan, kemampuan inovasi, efisiensi proses bisnis internal dan peningkatan kinerja dari aset tidak berwujud (Li, 2018;Maulana & Mulyana, 2020;Tseng & Lee, 2014).…”
Section: Dimensi Kinerja Organisasiunclassified
“…Dimensi finansial meliputi pengembalian aset (ROA), laba atas investasi (ROI), laba atas ekuitas (ROE), pangsa pasar, pertumbuhan penjualan dan profitabilitas. Sedangkan dimensi non-finansial meliputi kepuasan klien, kepuasan karyawan, kemampuan inovasi, efisiensi proses bisnis internal dan peningkatan kinerja dari aset tidak berwujud (Li, 2018;Maulana & Mulyana, 2020;Tseng & Lee, 2014).…”
Section: Dimensi Kinerja Organisasiunclassified
“…Insurer financial insolvency has been a theme of study and area of interest for the last decade. Maulana and Mulyana (2020) stated that insurance profit is one such concept that has been implemented to signify the overall incremental profit of the insurer derived from the writing of the insurance sector. (Zainudin et al 2018;Dhiab 2021) found various firm-specific factors, including solvency ratio, age of companies, financial leverage, technical provision, premium growth, and claim ratio, that influence insurance companies' financial performance.…”
Section: Previous Studiesmentioning
confidence: 99%
“…After the brief introduction, it has been logically observed that a profuse amount of literature has been found globally that describes the general insurance paradigm in different ways for divergent states in different spans of time. Bansal and Singh (2021) quantified the insurance businesses planned on the stock exchange in six 'Gulf Cooperation Council (GCC) states (Maulana & Mulyana, 2020) investigated and established a link between economic insolvency and general insurers' productivity in the insurance sector of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%